Efficacy of Physiotherapy on Changes in Pain Value Based on Economic Status of Low Back Pain : Efektivitas Fisioterapi Terhadap Perubahan Nilai Nyeri Berdasarkan Status Ekonomi pada Nyeri Punggung Bawah - Kurniawan, Kartika Agung; Efendi, Arief; Halimah, Nurul (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2024)
Abstract Background: Low back pain is the third most common musculoskeletal disorder after osteoarthritis and rheumatism. Low back pain is a disease that is often found in the community. Low back pain is often the cause of a person feeling a decrease in ability in daily functional activities. Physiotherapy is one of the rehabilitation programs for low back pain. Aim: The efficacy of physiotherapy can be influenced by several factors, namely age, economic status and education level. This study aims to determine the effect of physiotherapy on changes in pain values based on the economic status of patients with low back pain. Method: This study assessed the effect of economic status on changes in pain scores in 52 subjects. The study design was a retrospective cohort without a control group for three months. Data were obtained from medical records and questionnaires and analyzed by regression test with dummy variables. Results: Regression test analysis with dummy variables showed a significance value between economic status and changes in pain scores after three months of physiotherapy of P=0.035 (R²=0.125, p<0.05). This means that economic status has an effect of 12.5% on the average change in pain value after physiotherapy. Conclusion: There is an effect of economic status on the average value of changes in the pain value of low back pain sufferers. Changes in pain values are better in patients with low back pain with low economic status compared to high and middle economic status.